Girls of Summer - Thayer, Nancy, 1943- (New York : Ballantine Books, 2020)
"From star-crossed matches to unexpected love triangles, summer on Nantucket always holds the promise of romance in this sensational novel from New York Times bestselling author Nancy Thayer. Lisa Hudson feels more alive than she has in a long time after hiring hunky carpenter Mack Whitney to renovate her old Nantucket home. There's no denying the spark growing between them--despite the fact that Mack is ten years her junior. But her twentysomething children, Juliet and Theo, on the island for the summer, worry that the new relationship will only lead to Lisa's heartbreak. Yet Juliet and Theo are in for tangled love stories all their own. When dreamy Ryder Hastings moves to the island to pursue a new environmental venture, Juliet feels an unwelcome attraction, her rocky romantic history pushing her to steer clear of love. Theo only has eyes for Mack's daughter, Beth, with whom he was bound by an unspeakable tragedy in high school--but can they overcome their past? By August, when an impending storm threatens to shatter the peace of the golden island, everyone discovers what they can and cannot control. Nancy Thayer dazzles again with this new tale of a magical summer"--.